2001
DOI: 10.1016/s0167-4781(01)00272-x
|View full text |Cite
|
Sign up to set email alerts
|

Gene structure and promoter function of a teleost ribosomal protein: a tilapia (Oreochromis mossambicus) L18 gene

Abstract: We have cloned and characterized a tilapia (Oreochromis mossambicus) L18 ribosomal protein gene, including the complete transcribed region and 488 bp of upstream regulatory sequences. We have also isolated two L18 cDNAs from another tilapia (Oreochromis niloticus) with a few conservative nucleotide differences. Our results suggest the presence of two genes in both species. Reporter constructs were tested for transient expression in CV1 cells and in microinjected zebrafish and tilapia embryos. The tilapia L18 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The tests were conducted using nucleotide sequences to determine whether singleton genes are under comparable evolutionary constraints, or whether they are subjected to different rates of evolution. Several methods have been incorporated into the Ka/Ks software calculator for the estimation of Ka/Ks ratios, which include NG (Nei & Gojobori, 1986), LPB (Molina et al, 2001;Pamilo & Bianchi, 1993), MLPB (modified LPB) (Tzeng et al, 2004), MLWL (modified LWL) (Tzeng et al, 2004), MYN (modified YN) (Zhang et al, 2006), and YN (Yang et al, 2009). The Ka/Ks_Calculator software uses a maximum-likelihood framework extended from the method of Zhang et al (2006), which takes into account transition/transversion rate ratio and nucleotide frequencies, and incorporates these evolutionary features into a codon-based model.…”
Section: Test For Natural Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tests were conducted using nucleotide sequences to determine whether singleton genes are under comparable evolutionary constraints, or whether they are subjected to different rates of evolution. Several methods have been incorporated into the Ka/Ks software calculator for the estimation of Ka/Ks ratios, which include NG (Nei & Gojobori, 1986), LPB (Molina et al, 2001;Pamilo & Bianchi, 1993), MLPB (modified LPB) (Tzeng et al, 2004), MLWL (modified LWL) (Tzeng et al, 2004), MYN (modified YN) (Zhang et al, 2006), and YN (Yang et al, 2009). The Ka/Ks_Calculator software uses a maximum-likelihood framework extended from the method of Zhang et al (2006), which takes into account transition/transversion rate ratio and nucleotide frequencies, and incorporates these evolutionary features into a codon-based model.…”
Section: Test For Natural Selectionmentioning
confidence: 99%
“…The regulation of the expression of genes is crucial for the accomplishment of their biological functions and is under the strict control of various regulatory elements including promoters, enhancers, and repressors (Gordon et al, 2009;Lettice et al, 2003;Vavouri et al, 2006). Promoters contain short motifs where transcription factors bind to regulate the transcription, and the sequences of many of them have been characterized in eukaryotic organisms, including fishes (Molina et al, 2001;Streelman & Kocher, 2002;Tchoudakova et al, 2001;Velan et al, 2015). Although the length and motif content of promoters, as well as their position relative to the 5′UTR, may vary considerably (up to several Kbp upstream of a gene's transcription start site, or TSS) (Placido et al, 2006), some core promoters can occur in short sequences from 100 to 300 bp upstream or downstream of the TSS (Smale & Kadonaga, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis on genomic structures of ribosomal protein genes has been reported in higher eukaryotes, such as human [8] and Xenopus [9]. Studies on promoter activity of ribosomal protein genes have been reported in various cell types [7,10], but only a few in both cells and zebrafish embryos [11]. Here we reported the molecular cloning of a pufferfish (Tetraodon fluviatilis) ribosomal protein L29 gene (TfL29) and performed the promoter assay in COS-1 cells and zebrafish embryos.…”
mentioning
confidence: 99%